Introducción a la lingüística hispánica - Hualde, José Ignacio (Cambridge University Press, 2001)
This is the ideal introduction to Spanish linguistics for students. Using clear explanations, it covers all the basic concepts required to study the structural aspects of the Spanish language - phonetics and phonology, morphology and syntax - as well as the history of Spanish, its dialects and linguistic variation. This second edition incorporates new features designed to enhance its usefulness for classroom teaching: chapters have been added on the sociolinguistics of Spanish in the USA, and on semantics and pragmatics. The chapter on syntax has been considerably expanded. Numerous exercises have been added throughout the book, as well as a new glossary to help with technical terms.